Thermodynamic investigation of a new combined cooling, heating, and power (CCHP) system driven by parabolic trough solar collectors (PTSCs): A case study. (25th December 2019) - Haghghi, Maghsoud Abdollahi; Pesteei, Seyed Mehdi; Chitsaz, Ata; Hosseinpour, Javad
Highlights: Thermodynamic study is performed for a system driven by parabolic trough solar collectors. A case study for summertime is developed for the school of engineering at Urmia University. The investigation is carried out in low, high, and no solar radiation modes during the day. Energy efficiency of low, high and no solar radiation modes are 98%, 47.3% and 98%, respectively. Exergy efficiency of low, high and no solar radiation modes are 17%, 8.3% and 17%, respectively. Abstract: A new solar-based, combined cooling, heating, and power system is designed and developed for the school of engineering at Urmia University in Urmia, Iran. The proposed arrangement consists of a solar subsystem with parabolic trough solar collectors, an organic Rankine cycle, two heating processes, and two single-effect absorption chillers. The system is thermodynamically studied for the summer air conditioning requirements, considering genuine energy demand and variable solar radiation in three different operational modes (solar, solar and storage, and storage modes). The influences on the system performance are assessed of varying three main variables including the number of days, organic Rankine cycle pump inlet temperature, and organic Rankine cycle turbine inlet pressure. The results demonstrate that the highest cooling, heating and electrical loads in the summer air conditioning are 896.9 kW, 228.5 kW, and 1500 kW, respectively. The energy load is provided by employing 449–1625 number of PTSCs throughout the year. Furthermore, for summertime the energetic and exergetic analyses reveal that the energy efficiency of the system in the solar mode, solar and storage mode, and storage mode is found to be 98%, 47.3%, and 98%, respectively. Accordingly, the exergy efficiencies were equal to 17%, 8.3%, and 17%.